GELIAT SASTRA KOTA PONTIANAK REFLEKSI KESASTRAAN PROVINSI KALIMANTAN BARAT - Khairul Fuad (tuahtalino, 2017)
Epicentrum of power often became center of civilization among those district. Capital town of epicentrum of power always became magnet of people majority too, so that complexity of activities being detected clearly. Pontianak Town as epicentrum of power at once capital town of West Borneo Province, became center of civilization indeed because of its people and their complexity of activities. Literature Stretched as a part of complexity of activities participated to get colouring dynamic of Pontianak Town life. For all this moment literature stretched more often happened at Pontianak Town because of its accessible easily than another towns at Province of West Borneo. Those literature stretched consisted of the launching, the performance, and the review of work of literature, wich ever happened at Pontianak Town. Those literature stretched of Pontianak Town became reflection literature of West Borneo. Therefore, data description through out collection of literature stretched events wich happened at Pontianak Town, denoted theory and methodology framework of this research. Therefore, data description throught collection of literature stretched events wich happened at Pontianak Town was as framework of theory and methodology of this study.